Maurice Blondel on the Mystic Life: Exchanges with Laberthonnière - Conway, Michael A. (Gregorianum, 2021)
It is well recognized in the secondary literature that Maurice Blondel made an exceptional contribution to the discussion of the mystical in the early years of the twentieth century in French circles. This article studies a particular forum in which Blondel developed his core ideas; namely, in his correspondence with his friend,Lucien Laberthonnière. The personal dimension to this exchange gives it a resonance that is particularly striking in terms of a contemporary appropriation of his thought.